Assessment of Microbial Contaminants and Antibiotic Susceptibility Patterns of Water Tank Samples from Selected Hostels in Ifite-Awka, Nigeria - Okafor, Ugochukwu Chukwuma; Eze, Chidera; Iloduba, Ugochukwu Samuel; Nwachineke, Chigozie Emmanuel (Tecno Scientifica Publishing, 2025)
This research assessed the microbial qualities and antibiotic susceptibility of bacterial isolates from water tank samples collected from ten hostels in Ifite-Awka, Nigeria. The samples were cultured on nutrient agar and Sabouraud dextrose agar, and morphological, biochemical, as well as microscopic analyses were carried out. The bacterial isolates included Staphylococcus aureus, Escherichia coli, Salmonella typhi, Bacillus cereus, and Bacillus subtilis. The fungal isolates included Mucor spp., Aspergillus niger, and Penicillium spp. The colonies ranged from 84 to 234 CFU/ml. Across all species, Levofloxacin and Pefloxacin demonstrated the highest activity, indicating broad-spectrum effectiveness. The poorest results were observed with Rifampicin and Gentamicin, as most isolates exhibited complete resistance. The resistance of coliforms such as E. coli and Salmonella typhi to some β-lactams suggested a potential case of antibiotic misuse within the community. Bacillus cereus exhibited the broadest resistance profile. In the fungal analysis, Mucor spp. was the most common (40%), while Aspergillus niger and Penicillium spp. each accounted for 30%. The presence of coliforms in 45% of the samples indicated poor hygiene and placed people’s health in jeopardy. The lack of routine water tank sanitation and consistent bacterial monitoring in the Awka region was particularly concerning given the presence of pathogenic bacteria and toxin-producing fungi. This research highlighted the importance of strict hygiene practices together with efficient cleaning techniques for water tanks in order to reduce microbial contaminants and coliform bacteria.